PWE-123 Haematological profile of oesophago-gastric cancers at point of diagnosis: a large single centre study. (17th June 2017) - Lourenco, F; Hossain, E; El-Ghazali, S; Kokri, G; Krishna, R; Kadri, S
Abstract : Introduction: Around 1 in 7 oesophago-gastric cancers (OGC) diagnosed via emergency admissions have advanced disease – being less suitable for curative therapy – highlighting the need for better surveillance. [1] NICE guidelines on OGC screening recommend that patients with upper gastrointestinal (GI) symptoms with low haemoglobin (Hb) or thrombocytosis be considered for non-urgent endoscopy – while iron deficiency anaemia warrants urgent endoscopy to look for lower GI cancers. [2] Low Hb, low MCV, thrombocytosis and leucocytosis have been suggested as being independently associated with OGC. [3] Method: This retrospective observational cohort study analysed haematological profiles (prior to histological diagnosis) of 590 patients with OGC over 3 calendar years (2014–2016). WHO guidelines were used to define anaemia [Hb <130 g/L (males) and <120 g/L (females)] – and further stratification was done based on severity [mild (>110 g/L), moderate (80–110 g/L) and severe (<80 g/L)]. We further sub-analysed patterns based on sex, age, tumour location and severity of anaemia. Results: Of the 590 patients, 285 (48%) were anaemic, of which 221 (37%) were normocytic, 51 (9%) were microcytic and 13 (2%) were macrocytic. Among 390 male patients, 194 (50%) were anaemic, of which 148 (38%) were normocytic and 38 (10%) were microcytic. Among 200 female patients, 91 (46%) were anaemic, of which 73 (37%) were normocytic and 13 (7%) were microcytic. Among 392 patients with oesophageal cancers, 123 (31%) were normocytic and 25 (6%) were microcytic. Among 198 patients with gastric cancers, 98 (49%) were normocytic and 26 (13%) were microcytic. There was a higher ratio of normocytosis to microcytosis seen in mild anaemia, when compared to moderate and severe anaemia. Leucocytosis and thrombocytosis were seen in 16% and 13% of all OGC patients respectively; more prevalent than microcytosis seen in only 9% of all patients. Conclusion: The higher prevalence of pre-diagnosis normocytic anaemia in OGC highlights the importance of prompt evaluation of any type of anaemia in patients suspicious of OGC – without focusing on low MCV or ferritin levels. Normocytic anaemia should be considered sufficient to trigger urgent investigations for OGC in patients with upper GI symptoms. References: . Healthcare Quality Improvement Partnership (HQIP). National Oesophago-Gastric Cancer Audit 2016. NHS Digital; 2016. . National Institute for Health and Care Excellence. Suspected cancer: recognition and referral. NICE Guideline NG12; 2015. . Stapley S, Peters T, Neal R, Rose P, Walter F, Hamilton W. The risk of oesophago-gastric cancer in symptomatic patients in primary care: a large case-control study using electronic records. Br J Cancer. 2013Jan 15;108(1):25–31. Disclosure of Interest: None Declared